KAJIAN LITERATUR : METODE PENGUJIAN KEAMANAN SISTEM APLIKASI BERBASIS WEB - Sapta Kusuma Azhari; Cakra Trinata; Besse Hartati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This document discusses the importance of information system security in the digital era, where much data and information is stored in website-based applications. Information system security is crucial to prevent various threats, such as data manipulation, information theft, and sabotage. This study aims to explore security testing methods, especially Penetration Testing, to identify and address vulnerabilities in web-based applications. The methods used in this study include a search for relevant literature, with a systematic approach using the PRISMA method. The results of the study indicate that there are several methods that are often used in application security testing, including Penetration Test, OWASP ZAP, and Vulnerability Assessment.